MICROWAVE-ASSISTED CENTRIFUGAL SPINNING OF GELATIN MICROFIBERS - Siimon, Kaido; Aung, Yu Yu (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2020)
MICROWAVE-ASSISTED CENTRIFUGAL SPINNING OF GELATIN MICROFIBERS. Herein, we disclose a method for preparing polymeric microfibers. According to an embodiment of the method, gelatin fibers were prepared from 50% aqueous gelatin solution by centrifugal spinning. The produced material feels similar to wool to the touch. Average fiber diameter was determined to be 40 ïm. Thermal stability of the material is similar to that of gelatin fibers prepared by other techniques, e.g. electrospinning. Elastic modulus of the fibrous material was determined to be 230 MPa and its toughness was found to be 160 kJ/m3. The described method is one of the fastest low-cost lab-scale fiber production techniques available (as a practical example, the speed of fiber production was roughly 5 g/s) and could be used to prepare various polymeric fibers in an eco-friendly way for a wide range of applications, including textile industry, tissue engineering and drug delivery.